PENGARUH BAHAN PENGEMAS DAN LAMA PENDINGINAN TERHADAP KEASAMAN DAN ANGKA REDUKTASE SUSU PASTEURISASI - Akhadiyah Afrila; Wahyu Windari (BUANA SAINS, 2010)
The objective of the research is to know effect the matter package and long refrigeration of acidity and reductase test on pasteurization milk. Material used 9 lt milk from lactating cow. Factorial of Completely Randomized Design (CRD) was used in this study. The first factor was kind of matter package and the second treatment is long refrigeration of 40C (0; 7; 14; 21 day), replicated three times. Variable observed were acidity and reductase test. The result showed that kind of the matter have no significant effect (P>0,05) on acidity and reductase test. Long refrigeration, interaction of the matter and long refrigeration have higly significant effect (P